The Impact of a Web-Based Course Concerning Patient Education for Mental Health Care Professionals: Quasi-Experimental Study - Laine A; Välimäki M; Löyttyniemi E; Pekurinen V; Marttunen M; Anttila M (JMIR PUBLICATIONS, INC, 2022)
Background: Continuing education has an important role in supporting the competence of health care professionals. Although Web-based education is a growing business in various health sectors, few studies have been conducted in psychiatric settings to show its suitability in demanding work environments.Objective: We aimed to describe the impact of a Web-based educational course to increase self-efficacy, self-esteem, and team climate of health care professionals. Possible advantages and disadvantages of the Web-based course are also described.Methods: The study used nonrandomized, pre-post intervention design in 1 psychiatric hospital (3 wards). Health care professionals (n=33) were recruited. Self-efficacy, self-esteem, and team climate were measured at 3 assessment points (baseline, 8 weeks, and 6 months). Possible advantages and disadvantages were gathered with open-ended questions at the end of the course.Results: Our results of this nonrandomized, pre-post intervention study showed that health care professionals (n=33) had higher self-efficacy after the course, and the difference was statistically significant (mean 30.16, SD 3.31 vs mean 31.77, SD 3.35; P=.02). On the other hand, no differences were found in the self-esteem or team climate of the health care professionals before and after the course. Health care professionals found the Web-based course useful in supporting their work and relationships with patients. The tight schedule of the Web-based course and challenges in recruiting patients to use the patient education program with health care professionals were found to be the disadvantages.Conclusions: Web-based education might be a useful tool to improve the self-efficacy of health care professionals even in demanding work environments such as psychiatric hospitals. However, more studies with robust and sufficiently powered data are still needed.